2004
DOI: 10.1111/j.1365-2621.2004.tb13366.x
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of in Apple Juice by Radio Frequency Electric Fields

Abstract: Heat pasteurization may detrimentally affect the quality of fruit and vegetable juices; hence, nonthermal pasteurization methods are actively being developed. Radio frequency electric fields processing has recently been shown to inactivate yeast in water at near-ambient temperatures. The objective of this study was to extend the radio frequency electric fields (RFEF) technique to inactivate bacteria in apple juice. A converged-field treatment chamber was developed that enabled high-intensity RFEF to be applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(51 citation statements)
references
References 19 publications
7
39
2
Order By: Relevance
“…Typically in RFEF and PEF processing, inactivation is dependent on field strength (Barsotti & Cheftel, 1999;Geveke & Brunkhorst, 2003, 2004b. However, a similar result to that observed in this study was reported for RFEF processing of apple juice (Geveke & Brunkhorst, 2004a). Inactivation increased as the electric field strength increased up to 16 kV/ cm.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Typically in RFEF and PEF processing, inactivation is dependent on field strength (Barsotti & Cheftel, 1999;Geveke & Brunkhorst, 2003, 2004b. However, a similar result to that observed in this study was reported for RFEF processing of apple juice (Geveke & Brunkhorst, 2004a). Inactivation increased as the electric field strength increased up to 16 kV/ cm.…”
Section: Resultssupporting
confidence: 87%
“…RFEF processing at 30 kV/cm and 20 kHz reduced the population of Saccharomyces cerevisiae in water by 3.8 log (99.98%) at 35°C (Geveke & Brunkhorst, 2003). RFEF processing at 21 kV/cm and 55°C inactivated Escherichia coli K12 in apple juice by 1.9 log (98.7%) relative to the control (Geveke & Brunkhorst, 2004a). Raising the temperature increased inactivation.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Therefore, factors present in the current study, that were not present in the study by Byrne et al (2006) may have attributed to the higher reduction of spores. These factors could include [1] the RF energy having a non-thermal effect on the inactivation of the spores (Geveke & Brunkhorst, 2003;Kozempel, Annous, Cook, Scullen, & Whiting, 1998;Ponne, Balk, Hancioglu, & Gorris, 1996;Geveke & Brunkhorst 2004); [2] the longer heating up times during RF cooking of PLM in the current study compared to those in Byrne et al (2006) may have thermally damaged the spores thereby giving an underestimate of the actual numbers present. However, a separate dedicated study would be required to determine the actual cause of these differences.…”
Section: Predicted Temperature Profiles and Pasteurisation Unitsmentioning
confidence: 93%
“…Although attraction is also reported, a reapetable test has not been verified. However, nonethermal effects of electromangetic waves on living tissue has been confirmed (Geveke & Brunkhorst, 2006). The imaginary part of the dielectric constant can be used to heat up a material remotely using radio waves.…”
Section: Introductionmentioning
confidence: 99%